The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1970
DOI: 10.1115/1.3425155
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Coupled Parallel Flows in a Channel and a Bounding Porous Medium

Abstract: Experiments were performed to study the laminar flow characteristics and the laminar-turbulent transition in a parallel-plate channel, one of whose bounding walls is a porous medium. The flow regime investigated herein is characterized by parallel, unidirectional, fully developed flows in the channel and the porous medium. The experimental results for the laminar regime were found to be in excellent accord with theoretical predictions based on a model which admits a slip velocity at the surface of the porous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
107
0
3

Year Published

1974
1974
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(115 citation statements)
references
References 0 publications
5
107
0
3
Order By: Relevance
“…The dotted curve corresponds to the no-slip case (s = 0) treated by Rouleau [22]. Further the slip constant α seems independent of fluid viscosity but depends on material parameter other than the permeability and in particular, on the porous surface characteristics [21,23].…”
Section: Mathematical Formulation and Solution Of The Problemmentioning
confidence: 99%
“…The dotted curve corresponds to the no-slip case (s = 0) treated by Rouleau [22]. Further the slip constant α seems independent of fluid viscosity but depends on material parameter other than the permeability and in particular, on the porous surface characteristics [21,23].…”
Section: Mathematical Formulation and Solution Of The Problemmentioning
confidence: 99%
“…Later, condition (1.2) was justified theoretically (Saffman 1971). It was discovered that the value of the slip coefficient ξ is strongly dependent on the local geometry of the interface (Beavers et al 1970;Richardson 1971;Taylor 1971). When describing a porous medium flow by the Brinkman equations instead of Darcy's law, more boundary conditions are required at the interface due to the spatial derivatives of the velocity.…”
Section: Introductionmentioning
confidence: 99%
“…This case of a porous medium surrounded by a Stokes flow has been a topic of active investigation with the main goal of deriving appropriate boundary conditions at the interface (Beavers & Joseph 1967;Beavers, Sparrow & Magnuson 1970;Richardson 1971;Saffman 1971;Taylor 1971;Neale & Nader 1974;Howes & Whitaker 1985;Goyeau et al 2003;Chandesris & Jamet 2006;Valdés-Parada, Goyeau & Ochoa-Tapia 2007;Tlupova & Cortez 2009;Valdés-Parada et al 2009, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence, both theoretical and experimental, suggests that Darcy's equation provides an unsatisfactory description of the hydrodynamic conditions, particularly near the boundaries of a porous medium. Beavers et al (1970) demonstrated experimentally the existence of shear within the porous medium near surface, where the porous medium is exposed to a freely flowing fluid, thus forming a zone of shear-induced flow field. Darcy's equation however, cannot predict the existence of such a boundary zone, since no macroscopic shear term is included in this equation (Joseph and Tao, 1964).…”
Section: Introductionmentioning
confidence: 99%